Perspectives on and from institutional ethnography - Reid, James, active 2017; Russell, Lisa, 1979- (Bingley, U.K. : Emerald Publishing Limited, 2017)
This book explores recent developments in Institutional Ethnography (IE) and offers reflective accounts on how IE is being utilised and understood in social research. IE is a sociological sub-discipline developed by Dorothy E. Smith that seeks to explicate the textual mediation of people's everyday experiences in their local sites of being. As an approach, IE is growing in significance across the globe, particularly in Canada, USA, Australia and UK. This collection includes contributions from those involved in the early development of IE alongside Smith as well as early career researchers, new to the sociology, theory and method of IE. Chapters focus on IE as a sociological theory and qualitative research method; the relationship between data generation and analysis in IE; implications from its findings for policy; and IE as a significant methodological approach. This involves explication of the theoretical, the operationalization of IE, and links between the theoretical and the empirical. It illuminates the relationship between data generation and analysis and includes consideration of its own textual relations of ruling.
Includes index.
Includes bibliographical references.
Keywords: Ethnology -- Methodology; Ethnology -- Research; Sociology